Building Positive Word Of Mouth: The Strategic Role Of Customer Value And Trust In Tax Consulting Services - Pertiwi, Mutiara; Dewi, Yuli Kartika; Herdinata, Christian (Community Engagement and Emergence Journal (CEEJ), 2026)
This study aims to empirically examine the influence of Customer Value and Trust on Word of Mouth (WOM) in the context of tax consulting services in Mojokerto, East Java. Using a quantitative approach and survey of 180 corporate taxpayers, this research analyzes the contribution of each variable to WOM after the consumption of tax consulting services. The results show that both Customer Value and Trust have a significant effect on WOM, both directly and through Trust as a mediating variable. The research model demonstrates strong predictive power with an R-Squared value for WOM of 0.896 and a Goodness of Fit of 0.796. The practical implication of this research is the importance for tax consulting firms to enhance customer value and build trust through high-quality service, transparency, and competence. These findings are expected to serve as a reference for companies, taxpayers, governments, and researchers on organic marketing strategies based on Word of Mouth in tax consulting services.